1998
DOI: 10.1007/bf02789092
|View full text |Cite
|
Sign up to set email alerts
|

Blood levels of copper, iron, zinc, and lead in adults in India and Pakistan and the effect of oral zinc supplementation for six weeks

Abstract: Deficiency in the intake of trace elements, such as copper (Cu), iron (Fe), selenium (Se), and zinc (Zn), is very common in the general population of most developing countries. A preliminary study in India and Pakistan showing the plasma levels of Zn and Fe indicates that approx 50% of the subjects who participated have low levels of both Fe and Zn, suggesting a marginal deficiency. The low plasma levels of these elements are more pronounced in females. The mean levels of Ze, Cu, and Fe in the plasma of 83 sub… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
3
0

Year Published

1999
1999
2021
2021

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 11 publications
(3 citation statements)
references
References 20 publications
0
3
0
Order By: Relevance
“…Studies have shown good correlation between cord blood zinc, maternal zinc concentration and birth weights (Bhutta et al, 1999;Murray and Lopez, 1997). This is critical to demonstrate because nearly 80% of infant mortality occurs in first 2 months of life (Schultink et al, 1997;Abdulla and Suck, 1998;Brooks et al, 2005). Any health programme that aims at reducing infant mortality rate needs to address mortality in the first two months of life.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Studies have shown good correlation between cord blood zinc, maternal zinc concentration and birth weights (Bhutta et al, 1999;Murray and Lopez, 1997). This is critical to demonstrate because nearly 80% of infant mortality occurs in first 2 months of life (Schultink et al, 1997;Abdulla and Suck, 1998;Brooks et al, 2005). Any health programme that aims at reducing infant mortality rate needs to address mortality in the first two months of life.…”
Section: Discussionmentioning
confidence: 99%
“…Neonatal mortality contributed to over 64% of the infant deaths particularly in those who were born low birth weight. Serious systemic infections like sepsis and pneumonia constituted 30 -40% of the causes of mortality Abdulla and Suck, 1998). This high prevalence of sepsis is likely to suggest an increased requirement for zinc in the young infants living in the developing countries.…”
Section: Discussionmentioning
confidence: 99%
“…Reasons for our null association may be that zinc found in supplements is in the inorganic form (bound to chloride, sulfate, oxides, or propionate) which may not be well absorbed (23,24), and that zinc absorption from supplements may be low when dietary intake is sufficient (25). However, results from randomized clinical trials have shown that zinc supplementation positively affects zinc plasma levels (26)(27)(28).…”
Section: Discussionmentioning
confidence: 99%